An in situ gelling system for bone regeneration of osteochondral defects. (November 2015) - Bellini, Davide; Cencetti, Claudia; Meraner, Joachim; Stoppoloni, Daniela; D'Abusco, Anna Scotto; Matricardi, Pietro
Graphical abstract: Highlights: Hyaluronic acid and gellan are used to form a new hydrogel system. The resulting hydrogel resemble a bottle capping. The hydrogel can be exploited for bone defects reparation. Primary human osteoblasts, seeded within the hydrogel, produce new tissue. Abstract: The aim of this study was the preparation of a very simple and, at the same time, innovative three-component in - situ gelling hydrogel, composed of hyaluronic acid, gellan gum and calcium chloride, for osteochondral defects reparation. The above mentioned biocompatible polymers were used in a smart combination for bone defects filling and capping, capable to form a very stable system that avoids the leakage of any material from it. The polymeric materials, obtained using various combinations of polymers/calcium ratios, were characterized in terms of rheological and dynamo-mechanical properties, degradation rate and adhesion to bone defects. In vitro biocompatibility tests, performed using human primary osteoblasts, showed that this novel system can be an ideal candidate for the regeneration of bone defects, potentially improving the surgery approach in this field.